Assessing Public Awareness and Socio-Economic Impacts of Drought in Bamyan Province - Safi, Lutfullah; Mushwani, Hayatullah (Journal of Natural Sciences – Kabul University, 2024)
The purpose of this research is to reveal the level of people's awareness and evaluate the economic and social effects of drought in the center of Bamyan province. Data were collected through a questionnaire, and then they were subjected to a thematic investigation. In this research, 372 residents of the center of Bamyan province participated. The findings of this study show that people's awareness of drought is at a reasonable level, but they know little about combating it. According to the responses, the social consequences of the drought were increased migration, reduced sources of clean water, and conflicts and unrest between families among people in the area under study. In addition, the findings of the research on the economic consequences show that the drought has caused a decrease in family income, a decrease in agricultural production, an increase in food consumption, a decrease in income, an increase in unemployment, and job losses.